Reconstruction of Mohs Defects Located in the Head and Neck. Issue 2 (March 2019) - Egeler, Sabine A.; Johnson, Anna Rose; Ibrahim, Ahmed M.S.; Bucknor, Alexandra; Chen, Austin; Malyar, Masoud; Tobias, Adam M.; Lin, Samuel J.; Mureau, Marc A.M.; Lee, Bernard T.
Abstract : Background: Defects following Mohs micrographic surgery (MMS) can range in size from small defects requiring linear closure to large defects needing flap coverage. Reconstruction is dependent on defect size and facial aesthetic unit involvement. The aim of this study was to review the types of facial reconstruction per aesthetic unit involvement and describe their outcomes. Methods: All data were retrieved for patients ≥18 years who underwent multidisciplinary treatment including dermatological MMS and plastic surgical reconstruction at a single tertiary hospital center (2001–2017). Patient characteristics, tumor pathology, surgical specifics, reconstructive modalities, and surgical outcomes were analyzed. Results: A total of 418 patients were included. Patients were predominantly White, non-Hispanic (97%) and female (58%) with a mean age of 60 ± 13.9 years. Tumor pathology was predominantly basal cell carcinoma in 73% of all cases followed by squamous cell carcinoma in 14%. The nasal aesthetic unit was mostly affected (50%). Local advancement flaps and different types of grafts were used in 51% and 25% of reconstructions, respectively. Complications were observed in 3% and local cancer recurrence in 4% of the patients. Scar revision was needed in 6% of the patients. Conclusion: Reconstruction of facial defects after Mohs micrographic surgery can be challenging due to its technical complexity and aesthetic implications. There were differences in complications in reconstructions performed within the same day versus 1 week, with a majority of complications occurring within same-day Mohs reconstructions. A multidisciplinary structured approach, which incorporates patient-reported outcomes, may be needed to optimize surgical results.